Public and private sector jobs, unreported income and consumption gap in India: Evidence from micro-data - Saibal Kar; Poulomi Roy; Sarani Saha (Institute for the Study of Labor (IZA), 2012)
This paper tries to document the presence of unreported income among public sector employees in India. We investigate empirically the wage gap as well as consumption expenditure parity between public and private sector workers. It tests the hypothesis that despite a lower level of public sector income in some of the quantiles, if the level of durable goods consumption between the private and the public sector employees are similar, then it might be indicative of the presence of unreported income among the public sector workers. The 2004-05 survey of income and consumption by workers in both private and public sectors (NSSO) supports presence of unaccounted for income among public sector employees at the uppermost quantile. The empirical part is followed by a generalized theoretical formulation that comes up with a measure of the equilibrium level of the unreported income earned by the public sector employees.
urn:nbn:de:101:1-201206146892
Keywords: C12; C31; D23; J21; 330; unreported income; consumption; indirect utility; quantile regression; India; Öffentlicher Dienst; Einkommen; Verbraucherausgaben; Vergleich; Privatwirtschaft; Indien